2012
DOI: 10.1103/physrevb.86.035435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen adsorption on the local properties of epitaxial graphene on SiC (0001)

Abstract: The effect of oxygen adsorption on the local structure and electronic properties of monolayer graphene grown on SiC(0001) has been studied by means of Low Energy Electron Microscopy (LEEM), microprobe Low Energy Electron Diffraction (µLEED) and microprobe Angle Resolved Photoemission (µARPES). We show that the buffer layer of epitaxial graphene on SiC(0001) is partially decoupled after oxidation. The monitoring of the oxidation process demonstrates that the oxygen saturates the Si dangling bonds, breaks some S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 38 publications
(34 reference statements)
4
39
1
Order By: Relevance
“…E-mail: Thomas.Seyller@physik.tu-chemnitz.de (Thomas Seyller) dependent [4] and it has been observed that this is a direct consequence of the presence of the buffer layer [10]. In recent years, various elements such as gold [11], lithium [12], silicon [13], fluorine [14], germanium [15], oxygen [16][17][18][19] and hydrogen [10,[20][21][22][23] have been intercalated between the buffer layer and SiC(0001) in order to modify the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: Thomas.Seyller@physik.tu-chemnitz.de (Thomas Seyller) dependent [4] and it has been observed that this is a direct consequence of the presence of the buffer layer [10]. In recent years, various elements such as gold [11], lithium [12], silicon [13], fluorine [14], germanium [15], oxygen [16][17][18][19] and hydrogen [10,[20][21][22][23] have been intercalated between the buffer layer and SiC(0001) in order to modify the interface.…”
Section: Introductionmentioning
confidence: 99%
“…From the observed π-plasmons in electron energy loss spectroscopy and graphene-related C1s core level components measured by x-ray photoelectron spectroscopy (XPS) they concluded that the buffer layer had been converted into graphene and that the latter remains undamaged by this process. Mathieu and coworkers [18] studied oxygen intercalation under MLG at higher temperature and lower oxygen pressure (T = 500 °C, p = 10 -4 torr, t = 3 h) and concluded that the buffer layer is partially decoupled from the substrate leading to bilayer graphene on an oxidized SiC(0001) surface. We have previously compared oxygen intercalation below the 6√3 buffer layer carried out under two different sets of conditions [17].…”
Section: Introductionmentioning
confidence: 99%
“…The local minimum in the LDOS indicated by the arrow is known to be to the position of the Dirac point (E D ) which is shifted with respect to the Fermi energy due to the strong charge transfer between graphene and the SiC substrate [17]. We find a Dirac Energy of E D ≈ -300 meV which implies a carrier concentration on the order of 10 13 cm -2 , characteristic of epitaxial monolayer graphene [18]. Carrier concentrations in this order are rather high in comparison to the ones measured for graphene produced by exfoliation or chemical vapor deposition (CVD) and can be reduced for instance with molecular doping [19].…”
Section: Cnrs-laboratoire De Photonique Et De Nanostructures (Lpn)mentioning
confidence: 94%
“…In order to investigate the effect of Au deposition on the electronic properties, we have performed local ARPES experiments (µARPES). [9,17,24] and is attributed to doping from the buffer layer [6,7]. On the 2D µARPES map, recorded after Au deposition (Figure 4b), the energy difference between the Fermi level and the Dirac point is still 0.40 ± 0.02 eV.…”
Section: Au Intercalation In Epitaxial Graphene On Sic(0 0 0 1)mentioning
confidence: 99%
“…Furthermore, Riedl et al [16] have shown that hydrogen intercalation can induce such desired decoupling. More recently, it was demonstrated that the oxygen can partially decouple the buffer layer from the substrate and reduce the intrinsic electron doping [17]. Moreover, the intercalation of metal clusters or molecules between the graphene layers may serve to functionalize graphene.…”
Section: Introductionmentioning
confidence: 99%